Oral manifestations, pathogenesis and drug modalities in individuals infected with SARS- CoV-2 (Bangladesh Journal of Medical Science, 2025)
The severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) that causes COVID-19 is a highly contagious disease that has had a significant global impact. A wide range of oral lesions have been reported in these patients. It is controversial whether these oral cavity manifestations are directly linked with the COVID-19 infection or are due to the patient’s systemic condition. Oral lesions in COVID-19 patients lead to difficulty in speech, mastication and deglutition. This article’s goal is to elaborate the typical oral lesions that people with COVID-19 disease manifest and possible drug modalities to management.BJMS, Volume: 24. Supplementary Issue 2025, Page : 39-44